2014
DOI: 10.4103/1673-5374.128217
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 attenuates activated microglia-induced neuronal damage

Abstract: The microglia-mediated inflammatory reaction promotes neuronal damage under cerebral ischemia/hypoxia conditions. We therefore speculated that inhibition of hypoxia-induced microglial activation may alleviate neuronal damage. To test this hypothesis, we co-cultured ginsenoside Rb1, an active component of ginseng, and cortical neurons. Ginsenoside Rb1 protected neuronal morphology and structure in a single hypoxic culture system and in a hypoxic co-culture system with microglia, and reduced neuronal apoptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…These cytotoxic factors are the major cause of neuronal damage and neuronal apoptosis through regulation of the Bcl-2 family [54,55,56]. The Bcl-2 family consists of pro-apoptotic (Bax and cleaved caspase-3) and pro-survival (Bcl-2) proteins, which are responsible for the physical and functional interactions that regulate apoptosis [57].…”
Section: Discussionmentioning
confidence: 99%
“…These cytotoxic factors are the major cause of neuronal damage and neuronal apoptosis through regulation of the Bcl-2 family [54,55,56]. The Bcl-2 family consists of pro-apoptotic (Bax and cleaved caspase-3) and pro-survival (Bcl-2) proteins, which are responsible for the physical and functional interactions that regulate apoptosis [57].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ginsenosides Rg1, Rg3, Rh1, Rh3, Rb1, Rk1, and Rf from Panax ginseng C.A. Meyer have been demonstrated to exhibit dual actions against neuroinflammation and hyperactivation of the HPA axis [ 106 , 108 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ], while 3,6’-disinapoyl sucrose and the oligosaccharide esters-enriched fraction, YZ50, from Polygala tenuifolia Willd have been shown to possess bioactivity that de-hyperactivates the HPA axis [ 216 , 217 , 218 ]. Additionally, poricoic acid A, isolated from Poria cocos (Schw.)…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 99%
“…The reduction of neurological deficits, brain oedema and BBB permeability are argued to underlie BBB protection. Further to this Ke et al ( 2014 ) demonstrated that ginsenoside Rb1 attenuates damage to rat cerebral cortical neurons against hypoxia-activated microglia. This neuroprotective mechanism may be mediated by the downregulation of nitric oxide, superoxide, and TNF-α expression (Ke et al, 2014 ).…”
Section: Plant Based Extractsmentioning
confidence: 83%